Assessing Business Empowerment Program Effectiveness: Dolago Padang's Women Farmer Group Study - Nur Syamsu; Suriani -; Sitti Aisya; Muthmainnah MD (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
This research evaluates the implementation of an economic empowerment program through the Women Farmer Group (WFG) using sustainable home food yard activities (P2L) supported by the Food Security Agency - Ministry of Agriculture. The program aims to enhance economic empowerment in priority areas, addressing stunting and vulnerable food-insecure regions while promoting food resilience. The study measures the effectiveness of the program implemented through the WFG and evaluates it from the perspective of Islamic economics. Adopting a field research approach with a qualitative descriptive method, primary data is collected through interviews and observations, and secondary data is obtained from the documentation. Program effectiveness is assessed using a simple statistical method, dividing realized program activities by the set targets. Analysis of effectiveness indicators is based on interview findings. The research measures program effectiveness through data reduction, presentation, and conclusion-drawing techniques. The results show that the WFG program in Dolago Padang Village fulfills two effectiveness indicators: target accuracy and program objectives. From the perspective of Islamic economics, the program aligns with principles of justice, responsibility, social security (Takaful), and economic empowerment by the principle of Palawan. However, the program needs to meet the remaining four effectiveness indicators. The study recommends strengthening program awareness and monitoring for future implementation. It emphasizes that achieving program success is a shared responsibility between the government and the community, requiring the fulfillment of effective measurement criteria.